2019
DOI: 10.2135/cropsci2019.01.0068
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Wild Relatives of Safflower to Increase Genetic Diversity for Fatty Acid Composition and Drought Tolerance

Abstract: Wild relatives of safflower (Carthamus tinctorius L.) may contribute genes to improve cultivated species under water stress conditions. This study was conducted to increase genetic diversity of safflower for agromorphological traits and fatty acid profiles using interspecific hybridization. Three species—C. tinctorius, C. palaestinus Eig., and C. oxyacanthus M. Bieb.—were used to develop three segregating populations of C. tinctorius × C. palaestinus (TP), C. oxyacanthus × C. palaestinus (OP), and C. oxyacanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
(50 reference statements)
2
4
0
Order By: Relevance
“…This finding agrees well with those reported by Janmohammadi et al. (2017) and Shahrokhnia and Sepaskhah (2017), who indicated the negative effects of drought stress on physiological and agronomic traits in safflower.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This finding agrees well with those reported by Janmohammadi et al. (2017) and Shahrokhnia and Sepaskhah (2017), who indicated the negative effects of drought stress on physiological and agronomic traits in safflower.…”
Section: Discussionsupporting
confidence: 93%
“…The high genetic variability detected for all the traits measured in this study has been reported elsewhere (Amini, Saeidi, & Arzani, 2008;Moradi & Ehsanzadeh, 2015;Shafiei-Koij et al, 2019); this is promising because the variability observed is essential for further genetic analysis and genetic improvement programs. On the other hand, the highly significant effects of the irrigation regimes revealed that all the measured traits were adversely influenced by water deficit.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Yield-components such as number of seeds per plant, number of capitula per plant, 1000-seed weight and number of capitula per plant are known as significantly positive traits for yield increasing in safflower [14,47], therefore combined selection criteria from these characteristics can efficiently improve the selection processes in breeding programs [14]. The safflower genotypes were selected for this study based on their field performance in a collection of $500 safflower accessions from diverse geographical origins.…”
Section: Relationship Between Safflower Accessions and Geographical Originsmentioning
confidence: 99%